BOUNDARY VALUE PROBLEM FOR THE PSEUDOPARABOLIC EQUATIONS - Ghorbanian, Siavash (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In the present paper the boundary value problem for the Sobolev type equation cases tL(u(t,x))+M(u(t,x))=f(t,x), t>0, x=(x_1,…,x_n)ΩR^n, u|_Ω=0, (Lu)(0,x)=g(z),xΩ,cases is considered, where L and M are second-order differential operators. It is proved that under some conditions this problem in the corresponding space has the unique solution.